Penerapan Flocking Behavior Untuk Pergerakan Berkelompok Non Player Character pada 2D Endless Runner Game - Yosua Yosua; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
2D Endless Runner Game is a game where the player will keep on moving forward thus no end point and will present obstacles for the player and keep the player's adrenaline driven to keep on playing. The obstacles on some of Endless game differs, for this research, the game which will be made will have differently obstacles such as obstacle and group movement. The game will have obstacle where there will be many opponents moving as a group to fight the player's character. The group of assailants which will fight the player, will be applied on simultaneously moving NPC. Flocking is the most famous methods from artificial intelligence which moves a group.Flocking's movement sometimes has this restrained moment, therefore, applied one of the pathfinding method that is A* to make the group's movement not be restrained. Based on this problem, the researcher will develop a game which will have assailant's group have the Flocking Behavior. The results of this study indicate that flocking can be applied in group movements and the resulting FPS affects the number of NPCs in the group This result was proven by testing 3 NPCs to produce FPS ranging from 43.6 and with 8 NPCs producing FPS around 33.7. NPCs also make it to the destination without being blocked.